2022
DOI: 10.1371/journal.pone.0265089
|View full text |Cite
|
Sign up to set email alerts
|

High mortality among hospitalized adult patients with COVID-19 pneumonia in Peru: A single centre retrospective cohort study

Abstract: Background Peru is the country with the world’s highest COVID-19 death rate per capita. Characteristics associated with increased mortality among adult patients with COVID-19 pneumonia in this setting are not well described. Methods Retrospective, single-center cohort study including 1537 adult patients hospitalized with a diagnosis of SARS-CoV-2 pneumonia between May 2020 and August 2020 at a national hospital in Lima, Peru. The primary outcome measure was in-hospital mortality. Results In-hospital mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…The study also highlighted the higher neutrophil count, ALT, AST, creatinine, and BUN in COVID-19 patients with severe symptoms and possible admission to the ICU [ 3 , 34 ]. Other biomarkers, such as LDH, PT, and D-dimer, were also associated with the severity of the disease and admission to the ICU [ 33 35 ]. Moreover, a report has found that patients with elevated leucocyte count tend to have more severe symptoms with possible admission to the ICU compared with nonsevere cases [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study also highlighted the higher neutrophil count, ALT, AST, creatinine, and BUN in COVID-19 patients with severe symptoms and possible admission to the ICU [ 3 , 34 ]. Other biomarkers, such as LDH, PT, and D-dimer, were also associated with the severity of the disease and admission to the ICU [ 33 35 ]. Moreover, a report has found that patients with elevated leucocyte count tend to have more severe symptoms with possible admission to the ICU compared with nonsevere cases [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study also found that ICU patients will have higher D-dimer and PT than nonsevere cases. It was reported that several laboratory tests, such as WBC count, platelet count, and C-reactive protein (CRP), are helpful to predict whether COVID-19 patients are likely to be admitted to the ICU [ 35 , 37 ]. Patients with a high WBC count and CRP are at a higher risk of severe disease and being admitted to the ICU [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the risk of COVID-19 morbidity and mortality increases with age. There is a higher frequency of deaths among patients aged 45 years or older ( Mas-Ubillus et al, 2022 ). Therefore, this study stratified the analysis by urban and rural status, and by older age group ( ≥ 45 years old, middle-aged and older adults) and younger age group (10–44 years old) separately.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, it spread rapidly worldwide, and the World Health Organization (WHO) declared a global pandemic on March 11, 2020 [ 2 ]. COVID-19 outbreaks in medical institutions are important, and can be associated with high mortality rates, especially amongst the elderly [ [3] , [4] , [5] , [6] ]. Although strict infection control measures to prevent nosocomial COVID-19 are crucial, the development of these may need to be tailored locally, because of the heterogeneity of hospitals and their patient populations [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…7 hospitals that did not have an isolation policy for patients confirmed or suspected with COVID-19 were excluded3 7 hospitals that did not have an isolation policy for patients confirmed with COVID-19 and 2 hospitals that did not perform aerosol-producing procedures were excluded4 7 hospitals that did not have an isolation policy for patients suspected with COVID-19 and one hospital that did not operate a screening clinic were excluded J o u r n a l P r e -p r o o f…”
mentioning
confidence: 99%